Analysis of Current Status of Water Pollution in the Yellow River Based on Principal Component. Issue 3 (March 2021) - Liu, Chang; Fan, Longjiang; Qin, Shipeng
Abstract: The Yellow River is the "mother river" of the Chinese nation. The Yellow River is vital to the economic, social development and ecological environment of the surrounding areas. In recent years, with economic development and the acceleration of urbanization, the water environment and water ecology in the Ningxia section of the Yellow River have been polluted to varying degrees. Therefore, it is urgent to investigate the pollution laws of the water environment of the Yellow River and carry out corresponding treatments. First, we extracted six major pollutant indicators from three aspects, and then we conducted a comprehensive evaluation of the water environment of a certain section of the Yellow River in the past 8 months: The entropy method is used to determine the weight of various pollutants' impact on the water environment, and the comprehensive evaluation index Q of water quality is obtained. Then the Q value of 8 months is compared with the actual data, and then the expected water environment (Type III water) Define the water environment comprehensive evaluation standard index Q_s, combine Q and Q_s to define the degree coefficient h reflecting the degree of water environment quality, and then divide the degree coefficient into intervals according to the principle of equal division, as the index of water environment classification. Finally calculated h=0.0088, according to the water quality grading index, it is concluded that the comprehensive water quality of a certain section of the Yellow River in the past 8 months has been classified as "poor", and it belongs to the very poor level in the "poor" category.